Pengaruh penggunaan tepung fleshing dalam pakan ayam pedaging terhadap kenaikan bobot ayam - Sutyasmi, Sri; Widowati, Titik Purwati; Susila, R. Jaka (Majalah Kulit, Karet, dan Plastik, 2002)
The  fleshing waste ratio of leather processing is very high, that was about 70-230 kgs/ton of raw material. Those waste containing high amount of protein. The aim of this experiment was to know the influenceof fleshing powder on the increasing of broiler body weight. This experiment was classified into two steps. The first step was focused on the preparation of fleshing powder. The second step was the application of fleshing powder as protein substitute of broiler feed. The results showed  that the quality of fleshing powder prepared by pressurize steaming at 2 atm for 15 min was better than by unpressurized method. The additional and the final weight of broilers feed by fleshing powder were not significantly difference with the control. Therefore, fleshing powder could be used as protein substitute on the prepraration of broiler feed instead of fish powder.  Key words : fleshing, protein powder,broiler feed, friendly environment.